Polypropylene and some Esterified Plants' Fibers Bio-based Composites - Nawal M Suleman; Eiman M. Eltyeb; Abuelgasim A. A. Mohammed (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
This study aimed to synthesize bio-based composites from polypropylene and some esterified plants' fibers extracted from khimp (leptadenia pyrotechnica), leaves, and fibers of the date palm tree (Phoenix dactylifera L.). 24 composites in form of sheets were synthesized by injection molding technique using a modified manually operated injection molding machine. Properties like density, melting range temperature, melt flow rate, molecular weight, melt viscosity and water absorption capacity were determined for each synthetic composite. The study employed MFR and ordinary laboratory tools. The study proved that the synthesized composites are of good process ability, physical and thermal properties and have more densities than polypropylene itself